ANALISIS EFEKTIVITAS REALISASI KINERJA KEUANGAN PAJAK DAN RETRIBUSI PARKIR TERHADAP OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) PEMERINTAH KOTA SURABAYA PADA TAHUN 2020-2022 - Joedith Erni Sukmawati; Antoni Antoni (CV. Adiba Aisha Amira, 2023)
This research is to analyze the effectiveness of parking taxes and levies on the optimization of local revenue. The unit of analysis in this research is the target and realization of parking tax and levy in 2020-2022. This research is a qualitative research. The focus and dimensions in this research are the results of the analysis of the effectivity ratio of parking taxes and retributions on the optimalization of Surabaya City's local revenue in 2022 and the case of illegal parking attendants who are still scattered in the zone/non-zone parking area managed by the regional apparatus. Data was taken using observation, interview and documentation techniques. Based on the results of the analysis of the effectivity of parking tax in 2020 is very effective at 101.81% of the specified target, but in 2021 and 2022 it is not effective against the specified target. So, it can be summarized that parking taxes and retributions are ineffective and contribute very little to the optimization of local revenue. For the Surabaya City Regional Revenue Agency and Transportation Agency, it is therefore necessary to explore the potential for tax revenue and parking levies in optimizing regional own revenue.